Chitosan-coated nanostructured lipid carriers for transdermal delivery of tetrahydrocurcumin for breast cancer therapy - Thien Hoang Truong (2022)
Chitosan (Ch)-coated nanostructured lipid carriers (NLCs) have great potential for transdermal delivery with high localization of chemotherapeutics in breast cancer. This study used tetrahydrocurcumin (THC), a primary metabolite of curcumin with enhanced antioxidant and anticancer properties, as a model compound to prepare NLCs. Response surface methodology was employed to optimize THC-loaded Ch-coated NLCs (THC-Ch-NLCs) fabricated by high-shear homogenization. The optimized THC-Ch-NLCs had particle size of 244 ± 18 nm, zeta potential of −17.5 ± 0.5 mV, entrapment efficiency of 76.6 ± 0.2% and drug loading of 0.28 ± 0.01%. In vitro release study of THC-Ch-NLCs showed sustained release following the Korsmeyer-Peppas model with Fickian and non-Fickian diffusion at pH 7.4 and 5.5, respectively. THC-Ch-NLCs demonstrated significantly enhanced in vitro skin permeation, cell uptake, and remarkable cytotoxicity toward MD-MBA-231 breast cancer cells compared to the unencapsulated THC, suggesting Ch-NLCs as potential transdermal nanocarriers of THC for triple-negative breast cancer treatment.